2019
DOI: 10.3390/ijms20246302
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hepatic Anti-Fibrotic Strategy Utilizing the Secretome Released from Etanercept-Synthesizing Adipose-Derived Stem Cells

Abstract: Tumor necrosis factor-α (TNF-α)-driven inflammatory reaction plays a crucial role in the initiation of liver fibrosis. We herein attempted to design genetically engineered adipose-derived stem cells (ASCs) producing etanercept (a potent TNF-α inhibitor), and to determine the anti-fibrotic potential of the secretome released from the etanercept-synthesizing ASCs (etanercept-secretome). First, we generated the etanercept-synthesizing ASCs by transfecting the ASCs with mini-circle plasmids containing the gene ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In previous studies, high-dosage TAA is known to induce lipid peroxidation and oxidative stress, and the pathological effects are mainly limited to ALI rather than causing direct damage to other organs ( Muller et al, 1991 ; Mladenovic et al, 2012 ). Thus, according to previous studies ( França et al, 2019 ; Han et al, 2019 ; Liu et al, 2021 ), we administered 250 mg/kg/day TAA to mice via intraperitoneal injection for 3 days to establish the ALI model in our present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, high-dosage TAA is known to induce lipid peroxidation and oxidative stress, and the pathological effects are mainly limited to ALI rather than causing direct damage to other organs ( Muller et al, 1991 ; Mladenovic et al, 2012 ). Thus, according to previous studies ( França et al, 2019 ; Han et al, 2019 ; Liu et al, 2021 ), we administered 250 mg/kg/day TAA to mice via intraperitoneal injection for 3 days to establish the ALI model in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…Male Institute of Cancer Research mice (ICR, 8 weeks old) were randomly divided into different groups, including control group, TAA group, Fer-1 pre-treatment and TAA group, or TAA with DFO group ( n = 6-9 mice per group). According to previous studies ( França et al, 2019 ; Han et al, 2019 ; Liu et al, 2021 ), TAA was injected (i.p., 250 mg/kg/day) for 3 consecutive days to induce acute liver injury. Fer-1 was administered (i.p., 2.5 μM/kg/day) for 3 days before TAA treatment ( Wang et al, 2017 ), and DFO (200 mg/kg/day, i. p) was injected with TAA for 3 days ( Mansour 2000 ; Wu et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…TNF-α-driven inflammation plays a key role in the occurrence of liver fibrosis. Han et al [ 37 ] designed genetically engineered ASCs that can produce etanercept (an effective TNF-α inhibitor) to play an anti-fibrosis role. They transfected ADSCs with a microcirculatory plasmid containing an insert encoding the etanercept gene to generate synthetic etanercept ADSCs.…”
Section: Ways To Enhance Ascs Therapeutic Performancementioning
confidence: 99%
“…In order to enhance treatment effectiveness, various modifications were made, including the aforementioned antioxidant and eugenol pre-treatment, modification with various factors including mmu_circ_0000623 and etanercept, all exhibited enhanced abilities in treating liver fibrosis[ 30 , 31 , 34 , 37 ].…”
Section: Application In Fibrosis-related Diseasesmentioning
confidence: 99%
“…Studies have found that WD can further cause copper deposition in the liver and gradually progress from a mildly symptomatic liver inflammation to liver fibrosis even acute liver failure [ 3 ]. Accumulating research indicates that inflammation leads to activation of hepatic stellate cells (HSCs) and is a prominent driver of liver fibrosis [ 4 , 5 ]. Some genes such as C-X-C motif chemokine ligand 8 (CXCL8), mitogen-activated protein kinase 1 (MAPK1), AKT serine/threonine kinase 1 (AKT1), SRC proto-oncogene (SRC), vascular endothelial growth factor A (VEGFA), and interleukin 6 (IL-6) have been reported to active EGFR tyrosine kinase inhibitor (EGFR-TKI) resistance, Kaposi sarcoma-associated herpesvirus (KSHV) infection, and human cytomegalovirus (HCMV) infection pathways, leading to liver inflammation and HSCs activation and promoting the progression of liver fibrosis [ 6 10 ].…”
Section: Introductionmentioning
confidence: 99%